USING SCAFFOLDING TECHNIQUE TO IMPROVE THE WRITING ABILITY OF THE 11TH GRADERS OF SMAN 5 MATARAM - Isnaini, Yulia; Saukah, Ali; Prayogo, Johannes A (English Department of Faculty of Tarbiyah and Teachers Training, 2015)
This study was intended to apply scaffolding technique as a teaching technique to solve the problems in the teaching and learning of writing report text. The research design used in this study was a Collaborative Classroom Action Research which had been conducted in two cycles. The subjects of this study were 32 eleventh graders of XI IPA 6 at SMAN 5 Mataram in academic year 2012/2013. The research instruments used to get the data were interview, questionnaire, observation checklists, field notes, and writing task.This article highlights the potential of the scaffolding technique integrated through the process approach-with which students go through a write-rewrite process; prewriting, drafting, revising, editing, publishing Â in giving students chance to work in real, live process of how real writer engages in the process of writing. However, the most important finding is the technique could improve the ability of studentsâ writing ability in writing report text.